Strand Transfer and Elongation of HIV-1 Reverse Transcription Is Facilitated by Cell Factors In Vitro - Warrilow, David (Public Library of Science, 2010)
Recent work suggests a role for multiple host factors in facilitating HIV-1 reverse transcription. Previously, we identified a cellular activity which increases the efficiency of HIV-1 reverse transcription in vitro. Here, we describe aspects of the activity which shed light on its function. The cellular factor did not affect synthesis of strong-stop DNA but did improve downstream DNA synthesis. The stimulatory activity was isolated by gel filtration in a single fraction of the exclusion volume. Velocity-gradient purified HIV-1, which was free of detectable RNase activity, showed poor reverse transcription efficiency but was strongly stimulated by partially purified cell proteins. Hence, the cell factor(s) did not inactivate an RNase activity that might degrade the viral genomic RNA and block completion of reverse transcription. Instead, the cell factor(s) enhanced first strand transfer and synthesis of late reverse transcription suggesting it stabilized the reverse transcription complex. The factor did not affect lysis of HIV-1 by Triton X-100 in the endogenous reverse transcription (ERT) system, and ERT reactions with HIV-1 containing capsid mutations, which varied the biochemical stability of viral core structures and impeded reverse transcription in cells, showed no difference in the ability to be stimulated by the cell factor(s) suggesting a lack of involvement of the capsid in the in vitro assay. In addition, reverse transcription products were found to be resistant to exogenous DNase I activity when the active fraction was present in the ERT assay. These results indicate that the cell factor(s) may improve reverse transcription by facilitating DNA strand transfer and DNA synthesis. It also had a protective function for the reverse transcription products, but it is unclear if this is related to improved DNA synthesis.